A case of video-assisted thoracoscopic resection of malignant transformation of pulmonary recurrent respiratory papillomatosis - Dominguez, Dana A.; Martin, David T.; Velotta, Jeffrey B. (Journal of Thoracic Disease, 2017)
Recurrent respiratory papillomatosis (RRP) is a disease of the respiratory tract caused by infection with the human papillomavirus (HPV) and is characterized by multiple recurring papillomas throughout the respiratory tract. Although rare, extra laryngeal involvement carries the risk of malignant transformation in 3–7% of adults. We report the case of a patient with unmonitored juvenile onset RRP with pulmonary involvement found to have malignant transformation to squamous cell carcinoma (SCC). Incidentally found on chest radiography for mild chest wall trauma, she was found to have a large left lower lobe mass with pathology consistent with SCC. The patient underwent surgical management with thoracoscopic left lower lobectomy and mediastinal lymph node dissection followed by adjuvant chemoradiation for pathologic stage IIIA SCC. Surveillance imaging at 6 months shows no evidence of disease progression.